Immunoglobulin VDJ repertoires reveal hallmarks of germinal centers in unique cell clusters isolated from zebrafish (Danio rerio) lymphoid tissues - Waly, Doaa; Muthupandian, Aradana; Fan, Chia-Wei; Anzinger, Harrison; Magor, Brad G. (Frontiers in Immunology, 2022)
DNA mutagenesis during antibody affinity maturation has potentially oncogenic or autoimmune outcomes if not tightly controlled as it is in mammalian germinal centers. Cold blooded vertebrates lack germinal centers, yet have a functional Ig gene mutator enzyme, Aicda. In fish there are clusters of Aicda+ cells encircled by pigmented ‘melanomacrophages’ and we test the hypothesis that these clusters are functionally analogous to germinal centers. Sequenced IgH VDJ repertoire libraries from individual isolated clusters showed evidence of B-cell clonal expansion and VDJ somatic hypermutation. Construction of Ig clonal lineage trees revealed that unlike surrounding lymphoid tissue, each cluster is dominated by a few B-cell VDJ clonotypes having hundreds of mutated variants. Recruitment of B-cells to the clusters appears to be ongoing, as there are additional Ig clones having smaller lineages. Finally, we show evidence for positive selection for replacement mutations in regions encoding the antigen contact loops, but not in the framework regions, consistent with functional antibody modification. Melano-macrophages appear to trap the Ag used for post-mutation B-cell selection, performing a role analogous to the follicular dendritic cells of mammalian germinal centers. These findings provide insights into the evolution of the affinity maturation process, the improvement of fish vaccines and possibly also the workings of atypical ectopic germinal centers generated in several human diseases.